Molecular cloning and in vitro transcription of rat 4.5S RNAH genes. - Harada, F (1986)
4.5S RNAH (4.5S RNA associated with poly A containing RNA) has extensive homology to major interspersed repeat B1 in rodent genomes. We developed a new cloning technique for screening genomic library that eliminates the signal produced by repeated sequences or pseudogenes and applied it to cloning of 4.5S RNAH genes. Six phage clones (2, 3, 6, 9, 10 and 15) which hybridize with 4.5S RNAH were isolated from a rat gene library by this method. The restriction fragments containing the 4.5S RNAH locus were subcloned into plasmids and sequenced. Clones 2, 3, 9 and 15 contained one to five base substitutions in the coding region for 4.5S RNAH and were probably pseudogenes. In clone 2, the 4.5S RNAH locus was linked directly with the identifier sequence. Clone 6 contained three copies of the 4.5S RNAH gene (6a, b and c) which were clustered in the same direction within 455 base pairs. 6b was linked directly with 6c and ubiquitous repetitive DNA sequences B2 were inserted immediately after 6a and 6c. These three sequences as well as the sequence in clone 10 were colinear with rat 4.5S RNAH. In an in vitro transcription system, only clone 10 gave intact 4.5S RNAH.